KOMPARASI MODEL COLLABORATIVE COLLECTION DEVELOPMENT DAN JUST-IN-TIME COLLECTION DEVELOPMENT PADA PERPUSTAKAAN PENDIDIKAN - Santi Puji Astuti; Sri Rohyanti Zulaikha (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2023)
This study aims to answer the question of how the application of collaborative and just-in-time model collection development and how the comparison of the two models that have been applied to educational libraries. The method used in this research is a critical review method with a literature study approach. The writer made comparation and analyze between two articles which adopted in different model of collection development. The research findings are as follows: 1) The collaborative collection development model utilizes library networks to save budgets and accelerate collection availability, while the just-in-time collection development model applies a responsive access-based collection development approach. This policy is to provide the right and fast collection and save funds. 2) The difference between these two models is that the collaborative model requires a network so as to facilitate the process of both procurement together in order to create budget savings, while the just-in-time collection development is a single model that does not really require a network so that it has absolute autonomy.